Electrode-Geometry Control of the Formation of a Conductive Bridge in Oxide Resistance Switching Devices - Fujiwara, Kohei (2009)
Control of the formation of conductive bridge between the metal electrodes in planar-type resistance switching device was attempted. We demonstrated in Pt/CuO/Pt devices that, using a triangular seed electrode for soft breakdown, the position and the size of the bridge can be controlled. The decrease in the size resulted in the drastic reduction of operation voltage and current to the same level as in capacitortype stacked device. We argue that the planar-type device might have a certain advantage for future non-volatile memory application.